Equilibrium threshold strategies and social benefits in the fully observable Markovian queues with partial breakdowns and interruptible setup/closedown policy. Issue 6 (1st November 2020) - Aghsami, Amir; Jolai, Fariborz
ABSTRACT: This paper studies the equilibrium balking strategies in the single-server Markovian queues with partial breakdowns and interruptible/setup closedown policy. That means the server may fail at any point in time, no matter the server is idle or busy and the service continues at a slower rate instead of stopping service totally. When the system becomes empty, the server ceases to operate by a closedown time. If a customer arrives during the closedown period, the system starts the service immediately without a setup time. After the closedown period, the server needs a setup time before providing the service upon arrival. We presume that the customers decide whether to join or balk immediately after their arrival based on the reward-cost structure of the system. The fully observable case is discussed and the equilibrium threshold strategies and the equilibrium social benefits for all customers are derived. A numerical example and a case study for a bank system are investigated in this regard. Eventually, the effects of several parameters on the equilibrium thresholds, social benefits, balking probability, probability of empty system and stationary distribution are expressed.